2024
DOI: 10.1038/s42003-023-05671-8
|View full text |Cite
|
Sign up to set email alerts
|

A revised nomenclature for the lemur family of protein kinases

Gábor M. Mórotz,
Neil A. Bradbury,
Oana Caluseriu
et al.

Abstract: The lemur family of protein kinases has gained much interest in recent years as they are involved in a variety of cellular processes including regulation of axonal transport and endosomal trafficking, modulation of synaptic functions, memory and learning, and they are centrally placed in several intracellular signalling pathways. Numerous studies have also implicated role of the lemur kinases in the development and progression of a wide range of cancers, cystic fibrosis, and neurodegenerative diseases. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This approach revealed that KCC2 is intimately associated with LMTK3 in the brain, a poorly understood brain-specific transmembrane kinase. 21 , 22 , 23 Mechanistically, LMTK3 acts to target PP1 to KCC2 to mediate dephosphorylation of S940, leading to KCC2 inhibition. Accordingly, inhibition of LMTK3 increased KCC2 activity dependent on S940, reduced intracellular Cl accumulation, and reduced neuronal excitability and the severity of seizure-like events in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…This approach revealed that KCC2 is intimately associated with LMTK3 in the brain, a poorly understood brain-specific transmembrane kinase. 21 , 22 , 23 Mechanistically, LMTK3 acts to target PP1 to KCC2 to mediate dephosphorylation of S940, leading to KCC2 inhibition. Accordingly, inhibition of LMTK3 increased KCC2 activity dependent on S940, reduced intracellular Cl accumulation, and reduced neuronal excitability and the severity of seizure-like events in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Receptor tyrosine kinases (RTKs) are cell membrane receptors that mediate the actions of peptide growth factors in metazoan organisms. In humans, there are 55 RTKs organized into 19 subfamilies or classes, as it is now recognized that three kinases in the lemur class phosphorylate serine/threonine residues ( 1 , 2 ). Of these, five RTK classes are the most common across metazoan taxa: epidermal growth factor receptor (EGFR; Class I); insulin receptor, IGF1 receptor, and the insulin receptor-related receptor (InsR; Class II); platelet-derived growth factor receptor (PDGFR; Class III); vascular endothelial growth factor receptor (VEGFR; Class IV); and fibroblast growth factor receptor (FGFR; Class V) ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%